Risk assessment of the Acacia cyclops dieback pathogen, Pseudolagarobasidium acaciicola, as a mycoherbicide in the South African strandveld and limestone fynbos - Kotze, Louis Jacobus Daniel (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.